2015
DOI: 10.1021/am5068645
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Polypyridyl TG6 Dye for the Sensitization of Nanoparticle and Nanocrystallite Spherical Aggregate Photoelectrodes

Abstract: A ruthenium polypyridyl dye containing a hexasulfanyl-styryl modified bipyridyl group as ancillary ligand, coded TG6, is investigated as a sensitizer for ZnO-based dye-sensitized solar cells (DSSCs). The advantages of this dye are a broad wavelength absorption spectrum, a large loading in ZnO photoelectrodes, a significantly larger extinction coefficient compared to more classical Ru-polypyridyl dyes, and the formation of less agglomerate in the pores of the ZnO layers. TG6 has been used to sensitize ZnO nanor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…TiO 2 layer thicknesses of 5 and 10 μm were found to be optimal for demonstrating performance enhancement from TTA film incorporation, as discussed below. To verify the quality of our devices, we constructed a DPSC with a 25 μm TiO 2 layer, which yielded an efficiency of 5%, which is consistent with or better than prior reports. Interestingly, the thinner films optimized for demonstrating the TTA-UC enhancement yielded only slightly lower efficiencies of 4.3% and 4.7% for the 5 and 10 μm thick layers, respectively.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…TiO 2 layer thicknesses of 5 and 10 μm were found to be optimal for demonstrating performance enhancement from TTA film incorporation, as discussed below. To verify the quality of our devices, we constructed a DPSC with a 25 μm TiO 2 layer, which yielded an efficiency of 5%, which is consistent with or better than prior reports. Interestingly, the thinner films optimized for demonstrating the TTA-UC enhancement yielded only slightly lower efficiencies of 4.3% and 4.7% for the 5 and 10 μm thick layers, respectively.…”
Section: Resultssupporting
confidence: 82%
“…As shown in Figure S3, the D131 molecule has a typical donor−π bridge–acceptor structure in which the indoline unit acts as the donor moiety, while cyanoacrylate acts as both the acceptor and the anchoring group to the surface of TiO 2 . Its absorption onset wavelength is 530 nm, which corresponds to a HOMO–LUMO gap of ∼2.34 eV. Under operating conditions in a DSPC, the external quantum efficiency (EQE) spectrum, referring to the number of incident photons at a given wavelength that successfully produce charged carriers, broadens and the absorption onset is considerably red-shifted to 575 nm (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…The basic approach for addition of sodium acetate was the addition of excess acetate ions that gives different particle morphologies than the particles synthesized in absence of sodium acetate. Sodium acetate causes a weak hydrolyzation, which controls the release rate of OH − [36] , [37] , [38] , [39] , [40] , [41] , [42] .…”
Section: Methodsmentioning
confidence: 99%
“…The conductivity measurements showed that the NR layers were more conducting than the aggregate particles. The electrical connections were much better for the NRs compared to the submicrometer spheres. , Moreover, a metal oxide-based composite, as well as the polymer conjugated, was emerged as CBLs in inverted PSCs, in which polymers can passivate the surface defect of metal oxides. The device output based on these composites is improved in comparison with pure metal oxides because of the increased electron selectivity of such composites. According to the previous study, Jia et al reported a cathode buffer interfacial layer composite from ZnO as well as PFN (poly­[(9,9-bis­(3′-( N , N -dimethylamion)­propyl)-2,7-fluorene)- alt -2,7-(9,9-dioctyl)-fluorene]) based on PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical connections were much better for the NRs compared to the submicrometer spheres. 37,38 Moreover, a metal oxide-based composite, as well as the polymer conjugated, was emerged as CBLs in inverted PSCs, in which polymers can passivate the surface defect of metal oxides. 39−41 The device output based on these composites is improved in comparison with pure metal oxides because of the increased electron selectivity of such composites.…”
Section: ■ Introductionmentioning
confidence: 99%